Design, characterization, and biological evaluation of curcumin-loaded surfactant-based systems for topical drug delivery - Fonseca-Santos B (Dove Medical Press, 2016)
Bruno Fonseca-Santos, Aline Martins dos Santos, Camila Fernanda Rodero, Maria Palmira Daflon Gremião, Marlus Chorilli School of Pharmaceutical Sciences, UNESP – São Paulo State University, Araraquara, São Paulo Brazil Abstract: From previous studies, it has been found that curcumin exhibits an anti-inflammatory activity and is being used for the treatment of skin disorders; however, it is hydrophobic and has weak penetrating ability, resulting in poor drug transport through the stratum corneum. The aim of this study was to develop liquid crystalline systems for topical administration of curcumin for the treatment of inflammation. These liquid crystalline systems were developed from oleic acid, polyoxypropylene (5) polyoxyethylene (20) cetyl alcohol, and water as the surfactant, oil phase, and aqueous phase, respectively. These systems were characterized, and polarized light microscopy showed anisotropy with lamellar mesophases (Formulation 1) and hexagonal mesophases (Formulations 2 and 3), which were confirmed by the peak ratio measured using small-angle X-ray scattering. In addition, rheological tests revealed that the formulations exhibited gel-like behavior (G'>G''), as evidenced by the increased G' values that indicate structured systems. Texture profile analysis showed that hexagonal mesophases have high values of hardness, adhesiveness, and compressibility, which indicate structured systems. In vitro studies on bioadhesion revealed that the hexagonal mesophases increased the bioadhesiveness of the systems to the skin of the pig ear. An in vivo inflammation experiment showed that the curcumin-loaded hexagonal mesophase exhibited an anti-inflammatory activity as compared to the positive control (dexamethasone). The results suggest that this system has a potential to be used as a bioadhesive vehicle for the topical administration of curcumin. Therefore, it is possible to conclude that these systems can be used for the optimization of drug delivery systems to the skin. Keywords: lamellar mesophase, hexagonal mesophase, liquid crystalline mesophase, self-assembly structures, water-surfactant-oil based-structures, curcumin, paw edema